THE IMPACTS OF THE USE OF GADGETS ON THE DEVELOPMENT OF CHILDREN 3-6 YEARS OF AGE - enny fitriahadi enny fitriahadi; Venaswari Hanna Tyastiti (SEAJOM: The Southeast Asia Journal of Midwifery, 2020)
Gadgets can indeed distract someone with the fun they get from these gadgets. Children are also affected by the latest technology because of the many applications offered in the gadgets, for example smartphones, that can change their habits to be immersed in a fun program in the gadgets they hold. Therefore, this study aims to determine the magnitude of the impact that can be produced by the use of gadgets on children, especially those aged 3-6 years. This research was conducted in a health post for children with a total of 26 respondents from the parents of the children studied. The instrument used was a questionnaire and a prescreening developmental format with Spearman rank for the statistical test. The result showed that there was a relationship between the use of gadgets and the development of children with a p value of 0.000. Parents’ control over the use of gadgets among children is needed to protect children from addiction that gives adverse impacts.